Altered grazing systems: pastoralism to conventional agriculture - Thornton, Philip K.; Herrero, Mario; Boone, Randall B. (Cambridge University Press, 2019)
A major characteristic of pastoral systems has been their endurance through time (1). The same cannot be said about many other agricultural land-use systems. A considerable literature exists on their evolution, rooted in the location geography developed by von Thu¨ nen in the early nineteenth century, and more recently in twentieth-century ideas around population growth and agricultural intensification (2–4).